MODEL PREVENTION OF COVID-19 IN PREGNANT MOTHERS AND FAMILY BASED ON LOCAL WISDOM : IN SONOAGENG VILLAGE BANYURIP HAMLET, PRAMBON DISTRICT NGANJUK DISTRICT - Nove Lestari; Nofi Juwitasari (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
Local wisdom is a person's attitudes and actions in response to changes in the physical and cultural environment, so that these attitudes and actions become new habits that must be carried out. The Local Wisdom-based Covid-19 prevention model is the use of local wisdom as an effort to prevent Covid-19 and as self-protection. Pregnant women are the main targets in preventing Covid-19 because changes in immunity that occur during pregnancy can make pregnant women more vulnerable to health problems, one of which is exposure to the Coronavirus. The purpose of this study was to determine the Covid 19 Prevention Model in Pregnant Women and Families Based on Local Wisdom in Sonoageng Village, Banyurip Hamlet, Prambon District, Nganjuk Regency. The research design is descriptive, with the research variable being the Covid-19 prevention model based on Local Wisdom. The population and sample are 30 respondents using the "Purposive Sampling" technique. The research instrument is a questionnaire, the research was conducted on February 14-15 March 2022, the data were analyzed by percentage and interpreted quantitatively. The results of the study found that 30 respondents, a small number of respondents had good knowledge with as many as 4 respondents (13%), with sufficient knowledge as many as 7 respondents (23%), and most respondents with less knowledge as many as 19 respondents (64%). Respondents' knowledge about the Local Wisdom-based Covid-19 prevention model is influenced by several factors, namely, age, education, occupation, and sources of information. It is hoped that the community, especially pregnant women, will be more active and more active in seeking information from the medical team or health team as well as electronic media about Covid-19 prevention based on local wisdom and following government policies so that they can break the chain of transmission of Covid-19 so as to reduce the number of pregnant women patients. positive for Covid-19.